A produção camerística para clarineta da década de 40 de Cláudio Santoro - Viana, Abner (2013)
This study entitled A Chamber Production for the Clarinet in the 1940s by Cláudio Santoro is based on how the composer related to the political, social and geographical changes of the 40s which acted directly on his work and urged him to seek other resources and tools of analysis and composition with teachers who influenced his musical career. This study also aims to contribute to the academic research and the enrichment of the repertoire of Brazilian music written specifically for the clarinet. Also contained in this research are the historical and political context of the first half of the twentieth century, the ideological standing of the composer, his career with the group Música Viva (phases with his mentor H. J. Koellreutter), and an approach to the problems concerning the aesthetic and evolution of musical language related to contemporary musical production in Brazil; the aesthetics of musical composition (in its four phases); proposals for revised editions of the five plays performed in score writing software, in which among the things established were the criteria for reviewing and editing based on practical chamber music study, and interpretive elements found in the scores related to the style of the composer for coherent interpretation. The methodology used was a historical and interpretive-performative research which sought to know, understand and explain the pieces proposed during the atonal-dodecaphonic periods of the composer, emphasizing the repertoire of contemporary Brazilian music. The sources used in the research were the following: musical literature, non-standardized interviews, electronic research, filmography and discography research and revised editions of scores. In others, attachments (sheet music, interviews and a biographical synthesis of the composer) and a product (a recording of five pieces in CD). *Keywords: Political-ideological aspects; Aesthetics of Music Composition, Performance in Chamber Music, Editing and Revision of Music Scores.